Modeling of the acute pyelonephritis in animals of various kind - A. V. Lukjanov; V. T. Dolgikh; E. G. Potievsky; B. A. Rais; T. F. Sokolova; V. M. Nikonov (Бюллетень сибирской медицины, 2006)
Experiments have been carried out with two kinds of laboratory animals: 27 rabbits of chinchilla breed with the age of 3—4 months and the weight of the body from 1740 to 2 290 grams (1 993,1 ± 243,2) and 49 white alley male rats with the weight of the body of 180—220 g (195,4 ± 27,3). As an infectious organism, the daily dredge hemolysinogen E. coli with colicinogenic factor Ca 38 was used. Roots of introduction of dredge E. coli were intravenous, transurethral, transcapsular in parenchyma kidneys, enteral and endotracheal (in rats). As the animals were infected through various entrance gates, three variants of acute infections of the uric system were obtained: purulent-destructive defeats, tubular-interstitial infringements and asymptomatic bacteriuria. High virulence of the urostrain E. coli , used in the experiment, is demonstrated. The hypothesis about the universal mechanism of infection of the uric system "from top to down", i.e. hematogenic, has been formulated.